Towards an internationalized and localized TEI - Rahtz, S (Institute for Research in Humanities, Kyoto University, 2006)
The Text Encoding Initiative Guidelines have been widely adopted by projects and institutions in many countries in Europe, the Americas, and Asia, and are used for encoding texts in dozens of languages. However, the Guidelines are written in English, the examples are largely drawn from English literature, and even the names of the elements are abbreviated English words. We need to make sure that the TEI and its Guidelines are internationalized and localized so that they are accessible in all parts of the world. The paper describes how the TEI project can develop internationally, including A review of why localisation and internationalisation matter A discussion of how the TEI architecture can be leveraged to support internationalised versions The application of the W3C ITS guidelines to the TEI work Practical results from a pilot project, and future translation plans The tools needed to make use of an internationalised TEI The steps towards ontologies in the TEI